FUNCTIONALITY OF FAMILIES OF ADOLESCENTS IN STATE SCHOOLS: A DESCRIPTIVE APPROACH - Francisca Georgina Macedo Sousa; Ítalo Rodolfo Silva; Andréa Cristina Oliveira Silva; Dennyse Cristina Macedo Silva; Ewaldo Santana (Universidade Federal do Paraná, 2012)
Family functionality is characterized as a structuring thread for constructing adolescents' behavior. This is an exploratory, descriptive and quantitative study, whose objective was to classify adolescents' families according to the Family APGAR (Adaptation, Participation, Growth, Affection, Resolution) involving 1035 adolescents from two state schools in a state in the Brazilian northeast. The data was collected by means of the Family APGAR, during lesson time, on days and at times defined by the school management, and analyzed through descriptive statistics, using an Excel database. 73,2% of the families were described as functional, and 26,8% as dysfunctional; the dimensions adaptation and dedication were related to the adolescents' greatest satisfaction. The results generate challenges for research, for the professional insertion of the nurse into the school context, as well as for interdisciplinary work and in the adolescent care network.